Novel disease-causing variant in RDH12 presenting with autosomal dominant retinitis pigmentosa. Issue 9 (24th May 2021) - Muthiah, Manickam Nick; Kalitzeos, Angelos; Oprych, Kate; Singh, Navjit; Georgiou, Michalis; Wright, Genevieve Ann; Robson, Anthony G; Arno, Gavin; Khan, Kamron; Michaelides, Michel
Abstract : Aim: To describe the clinical and molecular features of a novel, autosomal dominant RDH12 -retinopathy. Methods: Retrospective cross-sectional study. Twelve individuals from a four-generation British pedigree underwent ophthalmic examination, genotyping using next generation sequencing, including whole genome sequencing and multimodal retinal imaging including fundus photography, optical coherence tomography (OCT), autofluorescence imaging and adaptive optics (AO) scanning light ophthalmoscopy were performed. Visual electrophysiology was performed in a subset. Results: Eight family members were confirmed as affected by genotyping heterozygous for RDH12 c.763delG. Visual acuity ranged from −0.1 to 0.2 logMAR. Affected individuals had constricted visual fields. A parafoveal and peripapillary ring of hyper-autofluorescence was seen initially, and with progression the area of perifoveal hypo-autofluorescence increased to involve the parafoveal area. Mild retinal thinning was identified on OCT imaging with reduction in both foveal total retinal and outer nuclear layer thickness. Cone densities along the temporal meridian were reduced in affected individuals compared with normative values at all temporal eccentricities studied. One individual with incomplete penetrance, was identified as clinically affected primarily on the basis of AO imaging. Full-field electroretinography demonstrated a rod-cone pattern of dysfunction and large-field pattern electroretinography identified peripheral macular dysfunction. Conclusions: This novel heterozygous variant RDH12 c.763delG is associated with a rod-cone dystrophy with variable expression. Determination of the degree of penetrance may depend on the modality employed to phenotypically characterise an individual. This rare and specific heterozygous (dominant) variant is predicted to result in a gain of function, that causes disease in a gene typically associated with biallelic (recessive) variants.